2015
DOI: 10.1523/jneurosci.1685-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Interleukin-4 as a Modulator of Microglial Pathways and Ischemic Brain Damage

Abstract: After ischemic stroke, various damage-associated molecules are released from the ischemic core and diffuse to the ischemic penumbra, activating microglia and promoting proinflammatory responses that may cause damage to the local tissue. Here we demonstrate using in vivo and in vitro models that, during sublethal ischemia, local neurons rapidly produce interleukin-4 (IL-4), a cytokine with potent anti-inflammatory properties. One such anti-inflammatory property includes its ability to polarize macrophages away … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
222
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(230 citation statements)
references
References 58 publications
2
222
2
4
Order By: Relevance
“…16 In addition, a recent study demonstrated that injured neurons may release IL-4 at acute stages of stroke. 17 These results suggest that increased signaling through the IL-4 receptor may mitigate the inflammatory environment after stroke and lay the groundwork for recovery of neural function. Consistent with this hypothesis, we demonstrated that IL-4 deficiency significantly impairs sensorimotor and cognitive performance in two models of stroke, whereas IL-4 supplementation improves long-term functional outcomes after brain ischemia.…”
Section: Discussionmentioning
confidence: 91%
“…16 In addition, a recent study demonstrated that injured neurons may release IL-4 at acute stages of stroke. 17 These results suggest that increased signaling through the IL-4 receptor may mitigate the inflammatory environment after stroke and lay the groundwork for recovery of neural function. Consistent with this hypothesis, we demonstrated that IL-4 deficiency significantly impairs sensorimotor and cognitive performance in two models of stroke, whereas IL-4 supplementation improves long-term functional outcomes after brain ischemia.…”
Section: Discussionmentioning
confidence: 91%
“…IL-4 is known to regulate a variety of immune and inflammatory responses, including T cell differentiation and IgE class in B cells. [114] IL-4 is primary produced by TH2 cells. [115] During CD4+ cellular activation, cytokines are through T cell receptor mediated signaling and co-stimulation.…”
Section: Il-1βmentioning
confidence: 99%
“…The presence of M2 microglia favors tissue repair and studies involving mice lacking IL-4, which evokes transition towards the M2 phenotype, have shown that the outcome worsens in absence of M2 microglia [33]. In a recent study, it has been shown that IL-4 expression is enhanced in the penumbra of infarcted tissue, where it reaches its peak during the first 24 h [34]. Even though data regarding microglia is not available, it has been proven that M2 macrophages do express P2X7 [35].…”
Section: Discussionmentioning
confidence: 99%